1981
DOI: 10.1111/j.1471-4159.1981.tb00413.x
|View full text |Cite
|
Sign up to set email alerts
|

The Receptor‐Mediated Activation of Tyrosine Hydroxylation in the Superior Cervical Ganglion of the Rat

Abstract: The addition of carbachol to superior cervical ganglia causes a rapid increase in tyrosine hydroxylation in situ. The increase occurs in ganglia from both newborn and adult animals, and in ganglia from animals pretreated with reserpine. The increase is not due to increased transport of the substrate. The increase is dependent upon the presence of calcium, and is additive to the stimulation produced by dibutyryl cyclic AMP. The stimulation seems specific for tyrosine hydroxylation; dopamine beta-hydroxylation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

1983
1983
1987
1987

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…Evidence in favor of this idea includes the findings that cAMP concentrations in this ganglion can be increased by nerve stimulation or elevated K+ but not by dimethylphenylpiperazinium or bethanechol (17)(18)(19). These results, together with our findings and those of Ikeno et aL (16) that derivatives of cAMP increase dopa synthesis, raise the possibility that cAMP could be an intracellular mediator of the noncholinergic stimulation of TyrOHase.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Evidence in favor of this idea includes the findings that cAMP concentrations in this ganglion can be increased by nerve stimulation or elevated K+ but not by dimethylphenylpiperazinium or bethanechol (17)(18)(19). These results, together with our findings and those of Ikeno et aL (16) that derivatives of cAMP increase dopa synthesis, raise the possibility that cAMP could be an intracellular mediator of the noncholinergic stimulation of TyrOHase.…”
Section: Resultssupporting
confidence: 89%
“…If the increase in cGMP does occur in ganglionic neurons, it is possible that the same noncholinergic substance released by preganglionic nerve terminals might increase both cGMP and TyrOHase activity. However, cGMP is not likely to be a second messenger mediating the noncholinergic stimulation of TH activity because Ikeno et aL (16) and J. Horwitz (personal communication) found no effect on TyrOHase activity of incubating ganglia with derivatives of cGMP. cAMP concentrations may also be regulated by a noncholinergic, transsynaptic mechanism in the rat SCG.…”
Section: Resultsmentioning
confidence: 99%
“…7 and references therein). Analogues of cAMP have been reported to accelerate catecholamine biosynthesis in intact tissue preparations (8)(9)(10)(11). In broken cell preparations, tyrosine hydroxylase has been shown to be activated, in the presence of ATP and Mg2', by cAMP or cAMP-dependent protein kinase (e.g., see refs.…”
mentioning
confidence: 99%
“…The effect of preganglionic stimulation on tyrosine hydroxylase activity appears to be mediated in part by a nicotinic mechanism and in part by a noncholinergic mechanism (16). Nicotinic agonists, muscarinic agonists, and agents that raise ganglionic levels of cAMP all increase tyrosine hydroxylase activity in the ganglion (18)(19)(20). We have recently found that all of these agents also increase the phosphorylation of tyrosine hydroxylase in the SCG (21).…”
mentioning
confidence: 99%